Trends in business risk management research: A bibliometric analysis [Tendencias en la investigación sobre gestión del riesgo empresarial: Un análisis bibliométrico] (2017)
The objective of this research is to examine the investigative tendencies in the area of enterprise risk management. The methodology consists of the bibliometric analysis of 155 academic publications related to the subject and provided by the Scopus database. Subsequently, the quantity, quality and structure indicators were calculated to be able to understand the evolution of this area of study. The results show that the United States, the United Kingdom and China are the countries where the theme is most studied and the topics that are trend lined are coverage, decision-making, derivatives and project management. It is concluded that the research on risk management is focusing on sub-themes such as reputational risk, fraud risk and exchange risk, showing that the literature on this subject has been specializing and focusing on the new market needs. © 2017, Universidad del Zulia. All rights reserved.